Addiction treatment : a strengths perspective - Van Wormer, Katherine S.; Davis, Diane Rae (Boston Cengage learning, 2018)
"ADDICTION TREATMENT covers the biological, psychological, and social aspects of alcoholism, eating disorders, compulsive gambling, and other addictions. The authors bridge the gap between the popular twelve-step and harm-reduction approaches, thus illuminating how practitioners can guide clients down a trusted path that is tailored towards the client's particular needs. Through a number of first-person narratives about the experience of addiction, students will discover a realism and depth not commonly found in textbooks."--
The nature of addiction -- Historical perspectives -- Substance misuse, dependence, and the body -- Substance misuse with a co-occurring mental disorder or disability -- Gambling, eating disorders, shopping, and other behavioral addictions -- Addiction across the life span -- Screening and assessment -- Strengths-and evidence-based helping strategies -- Mutual help groups and spiritual/religious resources -- Family risks and resiliencies -- Ethnicity, culture, and the socioeconomic determinants of addiction -- Gender, sexual, and sexual orientation differences -- Public policy -- Appendix : Resources.
Includes bibliographical references (pages 536-624) and index.
Keywords: Addicts -- Rehabilitation; Drug addiction -- Treatment; Substance abuse -- Treatment; Alcoholism -- Treatment; Behavior, Addictive -- therapy; Substance-Related Disorders -- therapy; Addicts -- Rehabilitation; Alcoholism -- Treatment; Drug addiction -- Treatment; Substance abuse -- Treatment